Current Status of Gene Engineering Cell Therapeutics - Saudemont, Aurore; Jespers, Laurent; Clay, Timothy (Frontiers in Immunology, 2018)
Ex-vivo manipulationsmanipulation of autologous patient’s cells or gene engineered cell therapeutics haveshas allowed the development of cell and gene therapy approaches to treat otherwise incurable diseases. These modalities of personalized medicine have already shown great promises including product commercialization forin some rare diseases. The transfer of a chimeric antigen receptor (CAR) or T cell receptor (TCR) genes into autologous T cells has led to very promising outcomes for some cancers but also in oncology, and particularly for hematological malignancies. However, the main drawback of these autologous cell and gene therapy approaches is in product manufacturing, which is time-consuming, labor intensive and thus limits access of the therapy to larger patient populations. Allogeneic cell and gene therapy approaches could address some of these issues. In addition, gene engineered cell therapeutics are also being explored to induce tolerance and regulate inflammation. Here,Here we review the latest gene engineered cell therapeutic cell and gene therapy approaches being currently explored to induce an efficient immune response against cancer cells or viruses by engineering T cells, natural killer (NK) cells, gamma delta T cells or cytokine induced killer (CIK) cells and to modulate inflammation using regulatory T cells (Tregs)from autologous to allogeneic therapies.